Harput Tarihi Hoca Hasan Hamamının Özgünlüğünün Değerlendirilmesi - Şahin, Murat; Atıci, Kadir (Karabük Üniversitesi, 2025)
Farklı coğrafyalarda şekillenen kültürel yapılar, toplulukların yaşam biçimlerini yansıtan mekânsal düzenlemeler ortaya koymuştur. Bu kültürel izlerin korunması, toplumsal süreklilik ve kimlik açısından önem taşımaktadır. Kültürel mirasın gelecek kuşaklara aktarılabilmesi için, anıtsal yapıların özgünlük, tarihsel kimlik ve belgesellik niteliklerini yitirmeden korunması gereklidir. Tarihi yapıların bakım, onarım ve restorasyon süreçleri, yapıların tarihsel gelişimi ile doğrudan ilişkilidir. Bu bağlamda, mimari koruma sürecinde özgünlük ölçütü, eserin tarihî ve kültürel değerleri açısından büyük önem taşımaktadır. Kültürel mirasın özgün değerleriyle korunması, mimarlıkla birlikte tarih, sanat tarihi, arkeoloji ve sosyal bilimler alanında da önemli bilgiler sunmaktadır. Uluslararası koruma ilkeleri doğrultusunda, bir yapının tüm mimari öğeleri analitik yöntemlerle değerlendirilmeli ve özgünlüğü titizlikle korunmalıdır. Çalışmanın amacı restore edilerek yeniden işlev verilen Elazığ İli, Harput Mahallesinde bulunan Hoca Hasan Hamamı’nın özgünlüğünün ne derecede koruduğu ortaya koymaktır. Çalışma kapsamında Hoca Hasan Hamamı’nın restorasyondan önceki ve sonraki durumları karşılaştırmalar yapılarak özgünlükleri kıyaslanmıştır. Bu çalışmanın tarihi yapılarda restore edilirken özgünlük bağlamında dikkat edilmesi konusunda katkılar sunması hedeflenmiştir.

Cultural structures shaped by different geographical contexts have produced spatial arrangements that reflect the lifestyles of communities. The preservation of these cultural traces is of great importance for social continuity and identity. In order to transmit cultural heritage to future generations, monumental structures must be preserved without compromising their originality, historical identity, and documentary value. The maintenance, repair, and restoration processes of historical buildings are directly related to their historical development. In this context, the criterion of authenticity plays a crucial role in architectural conservation, as it reflects the historical and cultural values of the structure. The preservation of cultural heritage with its original features provides significant information not only in the field of architecture but also in history, art history, archaeology, and the social sciences. In line with international conservation principles, all architectural elements of a building should be evaluated using analytical methods, and authenticity must be preserved meticulously. The aim of this study is to assess the extent to which the authenticity of the Hoca Hasan Bath, located in the Harput District of Elazığ Province, has been preserved following its restoration and adaptive reuse. Within the scope of the study, the pre- and post-restoration conditions of the Hoca Hasan Bath were compared to evaluate its authenticity. This study aims to contribute to the discourse on preserving authenticity during the restoration of historical buildings.
EVALUATION OF THE AUTHENTICITY OF THE HISTORICAL HOCA HASAN BATH IN HARPUT
Keywords: Architecture (Other); Mimarlık (Diğer)